PENGEMBANGAN MATERI KONSEP DIRI SOSIAL SISWA SMA - Arman, Mohammad; Arlizon, Raja; Rosmawati, Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The concept of social self is a necessity for humans because this is the need to socialize with other people in order for the direction of life in a community socializing with more clear and orderly. Thus the concept of social good self should be established at an early age so that future values of kindness will be conceptualized in practice socializing with people. However, during the time in school is still minimal effort to improve this social self-concept. Therefore need to develop students' social self-concept material sma. This material is prepared using methods of research and development (R & D). The purpose of this research is 1) Establishment of the material on social self-concept of students in the review of, systematics, image support, freshness and completeness of material support for video and games. 2) Measuring the quality of the material are arranged. This material is validated by the supervisor 1 & 2, guidance and counseling teachers and students of SMA Negeri 5 Pekanbaru. This material is tested with the allocation of a three-hour lesson (3x45 '). This material consists of a sense of social self-concept, types or aspects of social self-concept, the factors that affect social self-concept, self-concept of social function, the benefits of social self-concept, social self-concept formation. The results of this study indicated the quality of the materials produced are in the category of